Agricultural technology evaluation: some considerations - Wortmann, Charles S. (International Center for Tropical Agriculture, 1993)
This paper addresses considerations for agricultural technology evaluation at various levels. At the research level, considerations include the information need, the resources required to conduct the research and the probability of research success. At the field-level, agronomic feasibility and the impact of the technology on sustainability should be assessed. Expected micro-economic or farm level impact of the technology, especially the expected acceptability of the technologies and their effect on the ability of the farm to stay in business needs consideration. Concern for the environment and natural resource management means that technologies must be assessed in light of ecological sustainability at a regional level. A technology needs to be compatible with macro-economic forces and its sensitivity to changes in policies and capital availability, and its impact on labor availability needs to be considered. The probable effect of the technology on social justice, or equity, for poor consumers, poor farmers, rural poor and future generations merits consideration. A means of integrated these considerations into a technology evaluation procedure is presented.